Trunk stabilization and its rehabilitative effects in children with cerebral palsy - YILDIZ ÖZER, AYSEL (My University, 2022)
The trunk has a major role in providing dynamic stabilization in postural reactions. It also plays a critical role in supporting upper and lower extremity movements, loading, and protecting the spine. Trunk stabilization is the maintenance of trunk postural control and movement despite the disturbing effects of gravity, internal and external perturbations. Cerebral palsy (CP) is a non-progressive neurodevelopmental disease. Weak trunk control is common among children with CP. Trunk stability is important in rehabilitation because of its contribution to the child’s activity and participation. However, the results of trunk stabilization training in CP rehabilitation are limited, and few studies have emphasized the importance of trunk stabilization in CP. Considering the growing interest in supportive and novel rehabilitation methods in children with CP, this paper aimed to (i) describe the main features of neck and trunk stabilization (ii) summarize the possible therapeutic effects of neck and trunk stabilization methods based on different approaches in patients with CP. As a result, the literature demonstrates that these exercises benefit the rehabilitation process in reducing the negative effects of trunk instability. Increasing trunk stabilization with different techniques can improve the child’s upper-lower extremity skills, visual-perceptual functions and balance abilities

Postüral reaksiyonlarda dinamik stabilizasyonun sağlanmasında gövdenin rolü büyüktür. Ayrıca üst ve alt ekstremite hareketlerini destekleme, yüklenme ve omurganın korunmasında kritik önemi vardır. Gövde stabilizasyonu, yerçekimi, iç ve dış pertürbasyonların olumsuz etkilerine rağmen gövde postüral kontrol ve hareketin sürdürülmesidir. Serebral palsi (SP), ilerleyici olmayan nörogelişimsel bir hastalıktır. Zayıf gövde kontrolü, SP'li çocuklar arasında yaygındır. Çocuğun aktivitesi ve katılımına olan katkısı nedeniyle gövde stabilitesi rehabilitasyonda önemlidir. Bununla birlikte, SP rehabilitasyonunda gövde stabilizasyon eğitiminin sonuçları sınırlı olup SP'de gövde stabilizasyonunun önemine vurgu yapan çok az sayıda araştırma yapılmıştır. SP'li çocuklarda destekleyici ve yeni rehabilitasyon yöntemlerine artan ilgiyi göz önünde bulundurarak, bu makale (i) boyun ve gövde stabilizasyonunun temel özelliklerini tanımlamayı (ii) SP'li hastalarda farklı yaklaşımlara dayalı boyun ve gövde stabilizasyon yöntemlerinin olası terapötik etkilerinin özetini vermeyi amaçlamıştır. Sonuç olarak literatür, gövde instabilitesinin olumsuz etkilerini azaltmada bu egzersizlerin rehabilitasyon sürecine yarar sağladığını göstermektedir. Farklı tekniklerle gövde stabilizasyonunun arttırılması çocuğun üst-alt ekstremite becerilerini, görsel-algısal fonksiyonlarını ve denge yeteneklerini geliştirebilir
Serebral palsili çocuklarda gövde stabilizasyonu ve rehabilitatif etkileri
Keywords: Neck Stabilization; Trunk Stabilization; Exercise; Cerebral Palsy; Boyun ve Gövde Stabilizasyonu; Egzersiz; Serebral Palsi